Experimental of Environmental Development Using Continuous Solar Dryer With Solid Dehumidification For Coffee Drying - Parulian Siagian; Aprima A. Matondang; Andreas V. H. Simanjuntak; Budhi S. Kusuma; Joel Panjaitan; Andrean V. H. Simanjuntak (UIR PRESS, 2025)
As the tropical country, Indonesia has a sustainable solar energy for the farm products such as coffee. Indonesia’s coffee has been categorized as one of the biggest export products in the world and needs a development system to provide drying coffee beans with good quality. Therefore, this study comprehensively explains an experiment to develop a continuous solar air dryer with a hybrid system for drying coffee. The system has two different modes: off-sunny and sunshine hours. The heated air from the collector is driven into the drying chamber during the sunlight. The results show that the drying chamber's maximum temperature during daylight ranged from 40°C to 56°C and 9°C to 22°C warmer than the ideal environment temperature. Then, the coffee beans got the 12,7% moisture content in 107 hours in a solar dryer with solid dehumidification material. During off-sunlight, the air humidity reaches a 17% reduction and relatively consistent with air temperature. Furthermore, the benefit of this research can support the agricultural system without sunlight and apply a molecular sieve as a solar dehumidifier for the desiccant material in the drying chamber.